Initiating buprenorphine treatment for opioid use disorder during short‐term in‐patient 'detoxification': a randomized clinical trial. (20th August 2019) - Stein, Michael; Herman, Debra; Conti, Micah; Anderson, Bradley; Bailey, Genie
Abstract: Background and Aims: The effectiveness of linking people from short‐term in‐patient managed withdrawal programs ('detoxification') to long‐term, primary care‐based buprenorphine is unknown. We tested whether buprenorphine initiation during an opioid withdrawal program and linkage to office‐based buprenorphine (LINK) after discharge would increase engagement with office‐based buprenorphine and decrease illicit opioid use during the ensuing 6 months compared with standard withdrawal management (WM). Design: Single‐site randomized controlled trial. Setting: Short‐term in‐patient detoxification program in Massachusetts, USA. Participants: People with opioid use disorder ( n  = 115) who averaged 32.4 years of age, 68.2% male, 79.1% white, using illicit opioids on 27.3 of the last 30 days, were randomly assigned to WM ( n  = 59) versus LINK ( n  = 56). Intervention and comparator: Intervention was buprenorphine induction, in‐patient dose stabilization and post‐discharge transition to maintenance buprenorphine at an affiliated primary care clinic (LINK). Comparator was 5‐day buprenorphine managed withdrawal protocol (WM). Measurements: Mean 30‐day rate of use of illicit opioids (primary aim) and prescribed buprenorphine (secondary aim) at 1, 3 and 6 months. Findings: Compared with WM, participants in the LINK condition had lower illicit opioid use rates at days 12 [b = −6.81, 95% confidence interval (CI) = –9.69; −3.92, P  < 0.001], 35 (b = −8.55, 95% CI – 11.63; −5.47, P  < 0.001), 95 (b = −7.34, 95% CI = –10.59; −4.11, P  < 0.001) and 185 (b = −3.52, 95% CI = –7.07; 0.27, P  = 0.052). The LINK arm had higher prescription buprenorphine use rates ( P  < 0.001) at all assessments. Conclusions: Among people with opioid use disorder, initiation of, and linkage to, office‐based buprenorphine treatment post‐discharge reduced illicit opioid use and increased days of buprenorphine treatment for up to 6 months post‐discharge compared with an in‐patient detoxification protocol.